Commonsense Understanding of Concurrency: Computing Students and Concert Tickets. - LEWANDOWSKI, GARY; BOUVIER, DENNIS J.; TZU-YI CHEN; MCCARTNEY, ROBERT; SANDERS, KATE; SIMON, BETH; VANDEGRIFT, TAMMY (Communications of the ACM, 2010)
The article presents information on a study which investigated the teaching of concurrency in computer science. Two groups of computer science students were asked to come up with solutions to concurrency problems involving the sale of concert tickets. One group was composed of relatively advanced students, the other of neophytes. Although concurrency problems are typically considered an advanced topic, they have become particularly pertinent in the field, and the results of this study indicate that both neophytes and more advanced students tend to offer the same common-sense observations, and make similar types of common mistakes. This is said to indicate that concurrency can be usefully studied at the introductory level.